2019
DOI: 10.1038/s41467-019-13062-z
|View full text |Cite
|
Sign up to set email alerts
|

A fln-2 mutation affects lethal pathology and lifespan in C. elegans

Abstract: Differences in genetic background in model organisms can have complex effects on phenotypes of interest. We previously reported a difference in hermaphrodite lifespan between two wild-type lines widely used by C. elegans researchers (N2 hermaphrodite and male stocks). Here, using pathology-based approaches and genome sequencing, we identify the cause of this difference as a nonsense mutation in the filamin gene fln-2 in the male stock, which reduces early mortality caused by pharyngeal infection. We show how f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…Trials were conducted at 15˚C and 20˚C, which are permissive for development, and at 25˚C which induces dauer entry during development and dauer‐like behavior in class 2 daf ‐ 2 mutant adults. All alleles were crossed into a fln ‐ 2( + ) background to avoid the confounding effects of the fln ‐ 2(ot611) mutation, which reduces P frequency (Zhao et al, 2019). The resulting, deconvolved data includes survival data for the whole population, and for P and p subpopulations, plus the proportion of P deaths.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Trials were conducted at 15˚C and 20˚C, which are permissive for development, and at 25˚C which induces dauer entry during development and dauer‐like behavior in class 2 daf ‐ 2 mutant adults. All alleles were crossed into a fln ‐ 2( + ) background to avoid the confounding effects of the fln ‐ 2(ot611) mutation, which reduces P frequency (Zhao et al, 2019). The resulting, deconvolved data includes survival data for the whole population, and for P and p subpopulations, plus the proportion of P deaths.…”
Section: Resultsmentioning
confidence: 99%
“…Trials were performed at 25˚C and the class 1 allele daf ‐ 2(m41) and class 2 allele daf ‐ 2(e1370) were included, to be comparable to the original study in which effects on lifespan of allele class‐specific interactions between daf ‐ 2 and daf ‐ 12 were described (Larsen et al, 1995); we also included an additional class 1 allele, daf ‐ 2(e1368) . We recently reported that, when confounding effects of fln ‐ 2 are excluded, daf ‐ 12(m20) modestly reduces daf ‐ 2(m41) lifespan by increasing P death frequency (Zhao et al, 2019). In the present study, necropsy analysis revealed that daf ‐ 12(m20) increases P frequency in both wild type and class 1 but not class 2 daf ‐ 2 mutant backgrounds (Figure 6a–c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the Bristol N2 hermaphrodite strain from CGC is generally considered the wild-type (WT) strain, but in 2018 a user reported that this N2 strain contained the alh-2(ot588) mutation ( ). Recently, the Gems lab reported that the Bristol N2 male stock from CGC contains the fln-2(ot611) mutation [ 166 ]. These findings have been confirmed by our lab (unpublished findings).…”
Section: Important Considerations For Geroprotective Drug Screeninmentioning
confidence: 99%